2020
DOI: 10.1101/2020.09.04.283093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inferring Patterns of Hybridization and Polyploidy in the Plant GenusPenstemon(Plantaginaceae)

Abstract: Reticulate evolutionary events are hallmarks of plant phylogeny, and are increasingly recognized as common occurrences in other branches of the Tree of Life. However, inferring the evolutionary history of admixed lineages presents a difficult challenge for systematists due to genealogical discordance caused by both incomplete lineage sorting (ILS) and hybridization. Methods that accommodate both of these processes are continuing to be developed, but they often do not scale well to larger numbers of species. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…The occurrence of hybridization between species of Penstemon has been documented extensively, fueling speculation about the relationship between introgression and speciation in the genus. For example, hybridization has been linked to the occurrence of whole-genome duplication in several Penstemon species (e.g., Crosswhite and Kawano, 1965;Freeman, 1983;Broderick et al, 2011;Blischak et al, 2020), supporting early molecular studies that suggested polyploidization, and more generally, introgression, as potentially common mechanisms of speciation in the genus (Clausen et al, 1940;Keck, 1932Keck, , 1945Straw, 1955). Phylogenetic inquiries into Penstemon have also identified introgression as a key evolutionary process because it likely explains, at least in part, the high degree of discordance observed between gene trees (Wessinger et al, 2016;Wolfe et al, 2006Wolfe et al, , 2021.…”
mentioning
confidence: 99%
“…The occurrence of hybridization between species of Penstemon has been documented extensively, fueling speculation about the relationship between introgression and speciation in the genus. For example, hybridization has been linked to the occurrence of whole-genome duplication in several Penstemon species (e.g., Crosswhite and Kawano, 1965;Freeman, 1983;Broderick et al, 2011;Blischak et al, 2020), supporting early molecular studies that suggested polyploidization, and more generally, introgression, as potentially common mechanisms of speciation in the genus (Clausen et al, 1940;Keck, 1932Keck, , 1945Straw, 1955). Phylogenetic inquiries into Penstemon have also identified introgression as a key evolutionary process because it likely explains, at least in part, the high degree of discordance observed between gene trees (Wessinger et al, 2016;Wolfe et al, 2006Wolfe et al, , 2021.…”
mentioning
confidence: 99%
“…The extent to which some populations are isolated from one another despite the detected gene ow is likely an indicator of the presence of a larger ancestral population in recent geological time. This population is likely undistinguishable in our current analyses due to the recency of divergence of the section in which this species resides, and the genus more broadly (Blischak et al 2020;Wessinger et al 2016;Wolfe et al 2006;Wolfe et al 2021) This conclusion is compounded by the remarkably low inbreeding coe cient values seen across all eight populations. Five out of eight populations were found to have negative inbreeding coe cient values, indicating a departure from Hardy-Weinberg equilibrium and an excess of heterozygosity within populations (Johnson & Shaw 2015).…”
Section: Population Genetic Diversity and Structurementioning
confidence: 92%
“…The output from PURC is one alignment for each locus, which includes all the copies present in each of the accessions, labelled by their accession ID and coverage (the number of reads that constitute that sequence). Since its release, PURC has been used to investigate allopolyploidy in genus-level datasets in diverse plant lineages (Morales-Briones and Tank, 2019;Dauphin et al, 2018;Suissa et al, 2020;Blischak et al, 2020), in studies of cytotype variation within species (Kao et al, 2020), and for applications where polyploidy itself was incidental to the primary research questions (Kao et al, 2019;Chery et al, 2019;Wolfe et al, 2021;Frost et al, 2020). Most notably, Blischak et al (2018) created a program to adapt PURC to data generated by microfluidic PCR, reducing one of the main limitations of amplicon-based approaches (the time and expense associated with PCR itself).…”
Section: The Purc Approachmentioning
confidence: 99%